Changing Hearts and Plates: The Effect of Animal-Advocacy Pamphlets on Meat Consumption - Haile, Menbere; Jalil, Andrew; Tasoff, Joshua; Vargas Bustamante, Arturo (Frontiers in Psychology, 2021)
Social movements have driven large shifts in public attitudes and values, from anti-slavery to marriage equality. A central component of these movements is moral persuasion. We conduct a randomized-controlled trial of pro-vegan animal-welfare pamphlets at a college campus. We observe the effect on meat consumption using an individual-level panel data set of approximately 200,000 meals. Our baseline regression results, spanning two academic years, indicate that the pamphlet had no statistically significant long-term aggregate effects. However, as we disaggregate by gender and time, we find small statistically significant effects within the semester of the intervention: a 2.4 percentage-point reduction in poultry and fish for men and a 1.6 percentage-point reduction in beef for women. The effects disappear after two months. We merge food purchase data with survey responses to examine mechanisms. Those participants who (i) self-identified as vegetarian, (ii) reported thinking more about the treatment of animals or (iii) expressed a willingness to make big lifestyle changes reduced meat consumption during the semester of the intervention. Though we find significant effects on some subsamples in the short term, we can reject all but small treatment effects in the aggregate.